PENGUJIAN EFEKTIVITAS DIURETIK KOMBINASI EKSTRAK ETANOL DAUN AFRIKA (Gymnanthemum amygdalinum Del.) DAN DAUN KELAPA SAWIT (Elaeis guineensis Jacq.) PADA TIKUS JANTAN - Delisma Simorangkir (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2020)
African Leaf and palm leaf crops have a secondary metabolite content such as alkaloids and flavonoids that are efficacious as diuretics. The purpose of this study is to know the effectiveness of diuretics from the combination African leaf ethanol extract and palm leaf ethanol extract. Methods used Eksperiemental. The test of diuretic activity is conducted divided into 6 treatment groups. Each group consists of 3 tails of white rats. Group 1 (positive control) administered Furosemide 3.6 mg/kgBB, Group 2 (negative control) was given suspension Na-CMC 0.5%, group 3 without treatment as well as groups of 4.5, and 6 in a row administered a combination of African leaf extract doses and extracts Oil palm leaf ethanol in a row of